2006
DOI: 10.1177/1073191106290607
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Extent of Child Maltreatment Using Administrative Databases

Abstract: This study examined the extent of violence toward children and factors associated with child maltreatment in Florida using a cohort of children (N=499,330) who were adjudged to be victims of maltreatment between July 1, 1996, and June 30, 2003. To assess the extent of maltreatment, five indicators were proposed and examined. Multivariate analyses found that prior referral, having more than one type of maltreatment during an initial incident, and caregiver absence best predicted the recurrence of maltreatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 26 publications
1
35
0
1
Order By: Relevance
“…Caregiver substance misuse was strongly related to findings at the systems level with a number of studies focusing on the number of referrals and rereferrals to CPS for families with a substance-using caregiver compared to other families (Barth et al, 2006;McGlade, Ware, & Crawford, 2009;Yampolskaya & Banks, 2006). Consistently, having a substance-using caregiver was associated with a higher rate of referral to CPS, having a higher rate of rereferrals to CPS, and having a higher rate of substantiated cases within the system.…”
Section: Child Maltreatmentmentioning
confidence: 70%
“…Caregiver substance misuse was strongly related to findings at the systems level with a number of studies focusing on the number of referrals and rereferrals to CPS for families with a substance-using caregiver compared to other families (Barth et al, 2006;McGlade, Ware, & Crawford, 2009;Yampolskaya & Banks, 2006). Consistently, having a substance-using caregiver was associated with a higher rate of referral to CPS, having a higher rate of rereferrals to CPS, and having a higher rate of substantiated cases within the system.…”
Section: Child Maltreatmentmentioning
confidence: 70%
“…While a rich literature suggests that heavy drinking, alcohol abuse, and alcohol dependence are associated with physically abusive parenting, other studies have not found a positive relationship (Harter & Taylor, 2000; Widom & Hiller-Sturmhöfel, 2001). Additionally, a cohort study of children involved with the child welfare system in Florida found that reoccurrence of abuse was less likely in families that where perpetrator had used alcohol (Yampolskaya & Banks, 2006). These disparate findings may be due to how alcohol use was measured and the populations studied (Testa & Smith, 2009).…”
Section: Alcohol Use and Physical Abusementioning
confidence: 99%
“…For example, previous studies have reported that prior involvement with the child protection system was greatly associated with the likelihood of re-referral and recurrence of substantiated maltreatment. Similarly, families in which children died as a result of homicide had the highest proportion of substantiated referrals to the child protective services compared to families in which children died of natural causes or by accident (English, Marshall, Brummel, & Orme, 1999;Krous et al, 2006;Yampolskaya & Banks, 2006). Furthermore, when children from low-income families with prior maltreatment reports were compared to those without prior reports, much higher rates of death were found in a group with prior maltreatment reports (Jonson-Reid et al, 2007).…”
Section: Discussionmentioning
confidence: 81%